Urban Environmental Risk Mitigation using PS-INSAR Time Series and 2D Seismic Analysis in Bekasi Area, Indonesia - Novi Triany; Ildrem Syafri; Iyan Haryanto; Muhammad Burhannudinnur; Joko Widodo; Abang Mansyursyah Surya Nugraha; Ramadhan Adhitama; Himmes Fitra Yuda; Mira Meirawaty (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2026)
The Bekasi region experiences ground deformation that directly impacts urban environmental functions, including the effectiveness of risk mitigation in spatial planning. However, studies in Bekasi have mostly focused on land subsidence and have rarely integrated deformation patterns with subsurface structural controls. Aims: This study investigates urban ground deformation in Bekasi by integrating Sentinel-1A PS-InSAR time series and 2D seismic analysis as a basis for evidence-based risk mitigation. Methodology and results: Sentinel-1A SLC images acquired from December 2014 to January 2026 were processed using SARPROZ to obtain line-of-sight (LOS) velocity and displacement, then cross-checked against time-series displacements from the nearest CORS, and correlated with 2D seismic sections to evaluate subsurface geological conditions. PS-InSAR results show heterogeneous deformation (approximately -10 to +5 mm/yr). The values indicate dominant subsidence in the north and uplift in the south, which may be caused by both anthropogenic and tectonic factors. Seismic interpretation indicates geological structural segmentation. There is a W-E trending thrust fault in the south that is consistent with the Baribis active fault. Meanwhile, an N–S trending normal fault in the north indicates the reactivation of an old Sunda-pattern fault structure. Conclusion, significance, and impact study: Overall, these findings confirm that ground deformation in Bekasi is not spatially uniform and cannot be explained solely by anthropogenic processes. Therefore, risk mitigation strategies should be differentiated, such as improving the design and implementation of infrastructure and drainage systems in the north, and strengthening fault-zone-based zoning and screening critical infrastructure locations in the south.